The Impact of Warm Compresses on Pain Levels in Caesarean Section Patients - Royani Chairiyah; Ulfah Nuraini Karim; Moudy Emma Unaria Djami; Mella Yuria RA; Irwanti Gustina (Universitas Pendidikan Ganesha, 2025)
The high prevalence of postoperative pain among Cesarean Section (CS) patients directly affects recovery, early mobilization, and maternal comfort after delivery. This condition highlights the need to develop effective, safe, and affordable non-pharmacological interventions as complementary alternatives to analgesic therapy. This study aims to analyze the effectiveness of warm compress therapy in reducing post-CS pain levels and to explore patients’ subjective experiences of the intervention. A mixed-method approach was employed using a Randomized Controlled Trial (RCT) design involving 200 respondents divided into experimental and control groups. Quantitative data were collected using the Visual Analogue Scale (VAS), while qualitative data were obtained through in-depth interviews. Data were analyzed using t-tests, Wilcoxon tests, and Chi-Square tests with statistical software, alongside thematic analysis for qualitative findings. The results indicate that warm compress therapy significantly reduced pain intensity and was 2.19 times more effective in decreasing pain compared to the control group. Qualitative findings revealed four main themes: pain complaints, coping strategies, perceptions of warmth, and the benefits of warm compress therapy. In conclusion, warm compress therapy is proven to be an effective non-pharmacological intervention for managing post-CS pain. The practical implications suggest that warm compress therapy can be integrated into standard postoperative care protocols and utilized as evidence-based teaching material in nursing education to strengthen students’ clinical competencies in non-pharmacological pain management.